การจำลองระบบทำความเย็นสำหรับระบบทำความเย็นส่วนกลางแบบมหภาค - วรชาติ จิรัฐิติเจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The efficiency of energy used in Thailand becomes very important. Several methods for saving energy have been developed. For chiller cooling system, the central cooling plant is widely used. However, the district cooling plant is also interesting and it tends to be greatly used. The efficiency of such a plant depends on the pattern of selected equipments. These equipments should be suitable with the required cooling load. In this thesis, the computer program, named Cooling Equipment Selection, was developed as a basic guideline to select the pattern of equipments, i.e., number and size in cooling system in order to match with the required cooling load. The mathematical models of equipments, consisting of chiller, pump and cooling tower, were developed and put into the database s program. Four patterns for the distribution of chilled water piping, one pattern for the distribution of condensing water piping and subprogram for economic analysis were also considered. The program is tested with the 1000 tons maximum cooling load, while the load factor is varied between 0.458 and 1.000. It is found that at the load factor ranged from 0.458 to 0.588 the use of more than one chiller showed more advantage in saving energy than that of one chiller. Whereas at load factor ranging 0.692-1.000, one chiller is found to be more effective. However, when consider overall energy used in all equipments, at load factor 0.925-1.000, the use of one chiller tends give more energy saving than others. The net present value (NPV) is used as an economic analysis tool. It is found that at load factor 0.788-1.000, one chiller is found to be more suitable whereas at load factor 0.458-1.000, the number of chiller used in cooling plant should not be greater than three for 1000 tons maximum cooling load. On the other hand, it could be stated that energy used in cooling system is mostly consumed by chiller. In cooling tower, energy used shows insignificant amount compared to the total energy in system especially when the cooling system is large. In the primary chilled water pump, it is observed that head loss of piping system in power station also affects total energy used in the cooling system.